Indonesian Democracy as A Model for Egypt after The Arab Spring - Ahmad Sahide; Rezki Satris (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2021)
The Arab Spring in 2011 opened the way for democratization in some Arab countries, including Egypt. Egypt succeeded in overthrowing Hosni Mubarak as the president, but Egypt failed in consolidating democracy after holding a general election in 2012. The main factors of the failure in consolidating democracy in Egypt come from internal and external factors. The internal factor was that Egypt had not been ready for democracy , whereas the external factor was foreign intervention due to national interest. This article analyzes the failure of democratization in Egypt by using Jack Snyder and Georg Sorensen’s theory. In the last part of this article, the writer suggested that Egypt should have learned how to consolidate democracy from Indonesia. Indonesia is the best model of democracy for Egypt due to some reasons. The first one is Indonesia and Egypt near a culturally (religious approach), and the second one is Indonesia's success, as the majority Muslim state, in consolidating democracy since 1998.